In vitro cytotoxic and in silico activity of piperine isolated from Piper nigrum fruits Linn - Paarakh, Padmaa M. (In Silico Pharmacol, 2015)
BACKGROUND: Piper nigrum [Piperaceae], commonly known as black pepper is used as medicine fairly throughout the greater part of India and as a spice globally. PURPOSE: To isolate piperine and evaluate in vitro cytotoxic [antiproliferative] activity and in silico method. METHODS: Piperine was isolated from the fruits of P.nigrum. Piperine was characterized by UV,IR, (1)H-NMR, (13)C-NMR and Mass spectrum. Standardization of piperine was done also by HPTLC fingerprinting. In vitro cytotoxic activity was done using HeLa cell lines by MTT assay at different concentrations ranging from 20 to 100 μg/ml in triplicate and in silico docking studies using enzyme EGFR tyrosine kinase. RESULTS: Fingerprinting of isolated piperine were done by HPTLC method. The IC(50) value was found to be 61.94 ± 0.054 μg/ml in in vitro cytotoxic activity in HeLa Cell lines. Piperine was subjected to molecular docking studies for the inhibition of the enzyme EGFR tyrosine kinase, which is one of the targets for inhibition of cancer cells. It has shown −7.6 kJ mol(−1) binding and 7.06 kJ mol(−1) docking energy with two hydrogen bonds. CONCLUSION: piperine has shown to possess in vitro cytotoxic activity and in silico studies.